Trajetória da construção de um projeto interdisciplinar na escola: em foco a educação ambiental - Souza, Paulo Vitor Teodoro de (2014)
In this study we discuss the trajectory of constructing an interdisciplinary didacticpedagogical project in the dimension of Environmental Education. For development of the study, a bibliographical survey was carried out in regard to interdisciplinary pedagogical intervention and studies with a focus on Environmental Education. This allowed reflection on the simplistic manner of understanding this subject, perhaps by the absence of discussions in initial education of teachers. Eight teachers working in the 9th grade in a private school of primary education in Uberlandia, MG, Brazil were invited to prepare a didactic-pedagogical project. Of the eight teachers, four returned the questionnaire filled out and, of these, only two continue as teachers in the institution. These results led the researcher to include in the research not only preparation of the pedagogical intervention project, but also investigate the cause for the occurrence of this situation in the private school. Among the reasons, it was noted that teachers of the private school network are active in three or more different institutions and this may result in little teacher involvement with the school, as many work only one period in the institution and in a single day of the week. Three meetings were held with the participants and, based on the meetings, a didactic-pedagogical project for the institution was prepared as a product of this professional master’s study. So that this project may be applied in other educational institutions, the researcher prepared an expansion of the project, adapting the proposal to other contexts, since the context of a spring and lake in an educational institution is a specific context of a private school in the city of Uberlandia.